DAKWAH UNTUK PEMBERDAYAAN PEREMPUAN DALAM PEMBANGUNAN PERTANIAN DI PERDESAAN - Sholehah, Mar?atus (Jurnal Ilmu Dakwah, 2018)
This article is aimed at the description of many thoughts and ideas of da?wa about the role and the opportunity of woman who work in agriculture and repositioning the strategy of gender within the rural agricultural development policies. The double role of women is clearly indicating the importance of the double sources of income for a household. Women potentials, either as a housewife or as an individual of agricultural worker is the important factor to determine the success of gender strategy. The empowerment is suggested through applied and innovative technology, protection of working woman, improvement of training and extension activities, enhancement of regulations, facility support, increasing wage rate, and household industry skill development. Job opportunity is suggested to balance between male and female and encourage woman to participate in various development activities. With this, the gender strategy would improve household welfare in rural areas.****Artikel ini ditujukan untuk mendeskripsikan tentang pemikiran dan gagasan dakwah berdasarkan teori tentang peran dan peluang perempuan yang bekerja di bidang pertanian dan reposisi strategi gender dalam kebijakan pembangunan pertanian pedesaan. Peran ganda perempuan jelas menunjukkan pentingnya sumber penghasilan ganda untuk sebuah rumah tangga. Potensi perempuan, baik sebagai ibu rumah tangga atau sebagai individu pekerja pertanian merupakan faktor penting untuk menentukan keberhasilan strategi gender. Pemberdayaan disarankan melalui teknologi terapan dan inovatif, perlindungan perempuan pekerja, peningkatan pelatihan dan kegiatan penyuluhan, peningkatan regulasi, dukungan fasilitas, peningkatan tingkat upah, dan pengembangan keterampilan industri rumah tangga. Kesempatan kerja disarankan untuk menyeimbangkan antara pria dan perempuan dan mendorong perempuan untuk berpartisipasi dalam berbagai kegiatan pengembangan. Dengan ini, strategi dakwah terhadap perempuan akan meningkatkan kesejahteraan rumah tangga di daerah pedesaan.